FEDERALISM CRITICAL ARGUMENTS AS THE TRANSFIGURATIONS OF NIGERIAN FEDERALISM - Achinike, Hilary; Ogbonna, Stephens (Jurnal Ilmiah Peuradeun, 2016)
The debate concerning Nigeria’s political life has, in recent years, pervaded several fora as Nigeria’s political life remains under the shadow of an enigma. The basic tenets of federalism touched by a global wind of democracy, quite forceful in some regions of the world, are said to be a field and sweeping across all continents. But in contemporary Nigeria, as in Africa generally, authoritarianism reigns. Federalism critical arguments hold, in spite of its many global ‘bastard’ incarnates which in Nigeria shows as weak, emaciated and a pitiable thing. This paper argues that the body politic of Nigeria is congenially unreceptive to the reproductive seeds of a largely potent federalism. It is this ‘unreceptive environment’ that this paper has characterized as the transfigurations of Nigerian federalism.